Survey on pet owners awareness about parasitic diseases in cats and dogs and the preventive measure in Klang Valley - Ahmad, Nurafiqah (2016)
A cross-sectional study on level of pet owner awareness about cat and dog parasitic diseases and the preventive measure on Klang Valley was conducted from11th January to 31st January 2016. A random sampling was done to get 150 respondents who consulted from ten private veterinary clinics in Klang Valley area. A set of closed-ended structured questionnaire was designed for the study which includes client and pet profile and questions about knowledge about parasitic diseases and preventive medicine in cats and dogs. All data was collected in Microsoft Excel and analysed using S.P.S.S Version 12.0 for descriptive and analysis statistics. The awareness of pet owner about parasitic diseases and preventive medicine of cats and dogs were determined by their score from the questionnaire itself. From the descriptive analysis, 74% of the respondents were aware about parasitic diseases; whereas only 67% of the respondents awee aware about parasitic zoonosis. However, only 33% of the respondents were aware about preventive medicine such as deworming, ectoparasite control, and heartworm prevention medicine. In analytic analysis, Chi Square test was done to determine the association between educational status and the level of awareness of the respondents. The Chi Square test revealed that educational level have a significantly different to level of awareness of parasitic diseases but not statically significant with level of awareness of preventive medicine and parasitic zoonosis. In conclusion, majority of the pet owner still do not understand and aware about parasitic zoonosis. Thus many ways should be done to educate pet owners about parasitic zoonosis for both their knowledge and health.